Demographic Sustainability and Regional Development: The Cases of Alto Minho and Alto Alentejo - Susana Caldinhas; Maria de Nazaré Roca; Vasco Silva (European Regional Science Association (ERSA), 2001)
Demographic Sustainability and Regional Development: The Cases of Alto Minho and Alto Alentejo Maria Nazaré Oliveira Roca, Vasco Silva, Susana Caldinhas Centro de Estudos de Geografia e Planeamento Regional, Universidade Nova de Lisboa The paper is focused on the interrelationship of the demographic resources and sustainable development, illustrated by the case studies of two regions of Portugal: Alto Minho and Alto Alentejo. In the introduction, some concepts related to demographic sustainability and rural development are discussed. In the following sections, the main features of the two sub-regions and a brief diagnosis of the population structure and dynamics are presented. This serve as the basis for the identification of the strengths and weaknesses as well as of the opportunities and threats related to demographic sustainability of those regions. In the conclusion guideline for promoting sustainable development of Alto Minho and Alto Alentejo are presented.
Keywords: 330